RETRACTED: Forest fires dynamics during the Covid-19 pandemic (on the example the Volga Federal District, Russian Federation) - Fazylova Alsu; Nasyrova Elina; Kamaeva Elvira (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001